Weighted Mortality Method According to Multiple Causes of Death - Lisbeth Fernández González; Armando Humberto Seuc Jo; Carlos Antonio Rodríguez García (Revista Finlay)
Foundation: mortality study usually shows death as a single-caused phenomenon, so it is considered necessary to discuss methods which include in the analysis, all diseases recorded in medical death certificates. Objective: to identify the conditions under which the weighted multi-causal approach differs from the classical single causal approach. Method: a descriptive study was conducted and a weighting method was applied to calculate mortality rates from the multiple causes of death of medical death certificates and the classic method that exclusively uses the basic cause. The universe was the total of deaths in the first semester of 2016 in Havana according to death certificates. The causes in which the two methods showed greater differences were identified. Data processing was carried out using the statistical package IBM-SPSS version 21.0. Results: diseases such as heart disease, dementia and Alzheimer's, malignant tumors and asthma did not show differences between the rates calculated by both methods; diseases such as primary essential hypertension, diabetes mellitus and pneumonia, showed important differences. Conclusions: the weighted multi-causal method differs from the classic single causal method, as the cause of interest appears more as secondary and less as basic; the mortality rate according to the weighted multicausal method is higher than that of the classical method for the corresponding cause.